2014
DOI: 10.4236/psych.2014.56064
|View full text |Cite
|
Sign up to set email alerts
|

Happiness Decreases during Early Adolescence—A Study on 12- and 15-Year-Old Finnish Students

Abstract: Global and school-related happiness were measured in 339 Finnish ninth graders, about 86% of whom had participated in a study on the happiness of sixth graders three years earlier. Students filled out two questionnaires, the Subjective Happiness Scale (Lyubomirsky & Lepper, 1999) and the School Children's Happiness Inventory (Ivens, 2007). In addition, they chose items that they perceived would increase their happiness from a given list. Both global and school-related happiness had decreased since the sixth gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 76 publications
5
19
2
3
Order By: Relevance
“…Results revealed that age was negatively correlated with joy ( r = −.13, p =.01) –consistent with other recent reports (Uusitalo-Malmivaara, 2014) -- and positively correlated with sadness ( r =.23, p <.0005), anger ( r =.20, p <.0005), and self-directed-hostility ( r =.13, p= .01). However, age was not correlated with interest ( r =−.03, p =.51), disgust ( r =.05, p =.35), fear ( r =.00, p =.94), guilt ( r =.04, p= .46), shame ( r =.01, p =.80), or contempt ( r =.10, p= .06).…”
Section: Resultssupporting
confidence: 90%
“…Results revealed that age was negatively correlated with joy ( r = −.13, p =.01) –consistent with other recent reports (Uusitalo-Malmivaara, 2014) -- and positively correlated with sadness ( r =.23, p <.0005), anger ( r =.20, p <.0005), and self-directed-hostility ( r =.13, p= .01). However, age was not correlated with interest ( r =−.03, p =.51), disgust ( r =.05, p =.35), fear ( r =.00, p =.94), guilt ( r =.04, p= .46), shame ( r =.01, p =.80), or contempt ( r =.10, p= .06).…”
Section: Resultssupporting
confidence: 90%
“…This result is in opposition with the findings of Meuleners and Lee (), Dew and Huebner (), and the 1‐year follow‐up study of Suldo and Huebner (), which were reviewed earlier and only partly supports Goldbeck et al. () but is in congruence with Petito and Cummins (), Uusitalo‐Malmivaara (), and González‐Carrasco, Casas, Malo, et al. () follow‐up research when the latter used multi‐item scales.…”
Section: Discussioncontrasting
confidence: 66%
“…Moreover, school‐related individual items indicate a sharp decrease over the 2‐year period, particularly for boys. Frequency questions significantly corroborate this result as children tended in Time 2 to have lower agreement with “teachers treat me fairly,” “I feel safe at school,” and “I like going to school.” Uusitalo‐Malmivaara () argued that this decrease is a consequence of the increasing school challenges, peer problems, stress at school, and school dissatisfaction as children grow older. Generally, the findings from the Children's Worlds study underlined that Algeria along with the other developing countries of Nepal, South Africa, and Ethiopia score particularly highly on almost all questions concerning school (Rees & Main, ).…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of Suldo and Huebner's () study, all of the other samples used by researchers were rather small. This is also the case with some of the more recent publications, such as the ones by Tomyn and Cummins (), who used the 11‐point multi‐item PWI‐SC (Personal Well‐Being Index–School Children, by Cummins & Lau, ) with a sample of N = 351 Australian adolescents aged 12–20 and observed that 12‐ and 13‐year‐olds scored significantly higher than older participants, and Uusitalo‐Malmivaara (), who used the multi‐item 7‐point Subjective Happiness Scale (Lyubomirsky & Lepper, ) with a sample of N = 339 Finnish students aged 12–15 and found that both overall and school‐related happiness had significantly decreased during the 3‐year period.…”
Section: Growing Interest In the Decreasing‐with‐age Swb Tendencymentioning
confidence: 62%